2020
DOI: 10.3390/ijms21113832
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Induced miR-675-5p Supports β-Catenin Nuclear Localization by Regulating GSK3-β  Activity in Colorectal Cancer Cell Lines

Abstract: The reduction of oxygen partial pressure in growing tumors triggers numerous survival strategies driven by the transcription factor complex HIF1 (Hypoxia Inducible Factor-1). Recent evidence revealed that HIF1 promotes rapid and effective phenotypic changes through the induction of non-coding RNAs, whose contribution has not yet been fully described. Here we investigated the role of the hypoxia-induced, long non-coding RNA H19 (lncH19) and its intragenic miRNA (miR-675-5p) into HIF1-Wnt crosstalk. During hypox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…GSK3β acts as a molecular regulation switch while the role of its activation in tumor progression still remains a controversy. On the one hand, upon the stimulus by Wnt in hypoxia, the GSK3/casein kinase 1 (CK1)/Axin/adenomatous polyposis coli (APC) destruction complex in the cytoplasm disintegrates, and the unphosphorylated β-catenin translocates to the nucleus and recruits on HREs, which interacts physically with HIF-1 to promote cell survival and adaptation to hypoxia [31]. Additionally, a previous study revealed overexpression of GSK3β inhibited β-catenin and HIF-1α expression [32].…”
Section: Hdaci Repressed Hif-1α Expression Via Inhibiting Pi3k and Gsk3β Pathwaymentioning
confidence: 99%
“…GSK3β acts as a molecular regulation switch while the role of its activation in tumor progression still remains a controversy. On the one hand, upon the stimulus by Wnt in hypoxia, the GSK3/casein kinase 1 (CK1)/Axin/adenomatous polyposis coli (APC) destruction complex in the cytoplasm disintegrates, and the unphosphorylated β-catenin translocates to the nucleus and recruits on HREs, which interacts physically with HIF-1 to promote cell survival and adaptation to hypoxia [31]. Additionally, a previous study revealed overexpression of GSK3β inhibited β-catenin and HIF-1α expression [32].…”
Section: Hdaci Repressed Hif-1α Expression Via Inhibiting Pi3k and Gsk3β Pathwaymentioning
confidence: 99%
“…S3d). Recent studies showed that hypoxia could regulated GSK3β expression by HIF1α [ 35 , 36 ]. However, our study showed that silencing of GSK3α could inhibit HIF1α expression, while had no effect on GSK3β expression.…”
Section: Discussionmentioning
confidence: 99%
“…It was found up-regulated by HIF in several tumours including Glioblastoma [75,76] and colorectal cancer [77]. Recently it was described its role in controlling cell cycle by regulating Glycogen Synthase Kinase 3β (GSK-3β) activity and allowing β-catenin nuclear localization [78]. MiR-675 was found up-regulated in hypoxic non-small cell lung cancer where in addition to promoting cell proliferation, it acts on apoptosis by directly inhibiting the expression of p53 [79]; also in this case, through the induction of a single miRNA, HIF promotes tumour growth by acting simultaneously on several molecular pathways.…”
Section: The Hypoxia-induced Non-coding Rnasmentioning
confidence: 99%